The Apocrypha through history: the canonical reception of the Deuterocanonical literature - Gallagher, Edmon L. (Oxford University Press, 2025)
The deuterocanonical books, otherwise called the Apocrypha, have been a part of Christian Bibles for as long as there has been a Christian Bible. For just as long, there have been disputes about their authority. Are they canonical Scripture, or merely edifying literature? These opposing positions can be found in the Church Fathers of the fourth and fifth centuries, who in turn influenced the entire subsequent discussion. The deuterocanonical books were almost always considered beneficial, often canonical, though there emerged with the Reformation in the sixteenth century Christian writers who disputed even the value of these books, suggesting that they might pose dangers to the faithful. The Apocrypha through History surveys the entire history of this issue, with a concentration on materials in Hebrew, Greek, and Latin (for the earlier period) or English and German (for the later period). Edmon L. Gallagher explores the origins of the deuterocanonical books and their reception in Judaism and Christianity, with separate chapters on the New Testament, the patristic period, the Latin West, the Greek East, the Reformation, and the English Bible. At each stage, the book investigates who considered the deuterocanonical books to be fully canonical--or not--and why? The Apocrypha through History provides a thorough yet accessible examination of one aspect of the history of the Bible, concluding with a chapter reflecting on whether it makes a difference if one's bible includes the deuterocanonical books.